Job Satisfaction and Change Readiness: Moderating Role of Gender - Gupta, Khushi; Baral, Deep Kumar; Dhakal, Ajaya (International Research Journal of MMC, 2024)
Failing to assess employees' readiness for change can lead managers to waste significant time and effort managing resistance. This time could otherwise be spent productively. This study attempts to make a rigorous empirical examination of the effects of job satisfaction on change readiness along with assessing the moderating role of gender. The primary collection of data is done through likert scale and were analyzed by using IBM SPSS statistics version 23. On the other hand, the secondary data were taken from the articles, journals and website. Through a simple and dummy indicator regression analysis of the variables, it talks about the analysis's findings, which show that job satisfaction had a positive and significant impact on change readiness. This study implies that the value of coefficient of multiple determination is 0.299 which implies that the variation in CR can be explained by JS was 9.9%. Similarly, gender was no moderating the effects of job satisfaction on change readiness shown by the dummy indicator regression analysis. While acknowledging that there is no established theory describing the relationship between these two major constructs in organizational behavior, this study attempts to provide some of the empirical support that there was positive significant association between job satisfaction and change readiness. This study determined the value of R is to be .547a. This paper includes with the number of implications and research direction for both academic and organizational managers, Job satisfaction plays a critical role in determining employees' readiness for change, with higher satisfaction leading to increased acceptance and enthusiasm for change efforts.